Mudanças no regime do icms: uma estimativa da perda fiscal decorrente da desoneração das exportações e impactos sobre a balança comerciar - Honorio Kume; Guida Piani (Economia Aplicada, 1997)
Recently the Brazilian Congress passed a law exempting exports of basic and intermediate products from the mostimportant value added tax in the country — the ICMS — and allowing for the rebate ofthat tax payed on the purchase of capital goods and consumption goods indirectly used in the production process. These measures stand for a "fiscal" devaluation that is expected to improve the performance of Brazilian tradable goods. This paper presents an estimate of the value of the ICMS revenue originating in export activities in 1994 and 1995, as well as an evaluation of the impact of the fiscal burden reduction on the Brazilian trade balance